The "Hospital Real de San Josef de los Naturales" and the rheumatic conditions found in New Spain during sixteenth century - F.J. Aceves-Avila; M.A. Delgadillo-Ruano; C. Ramos-Remus; A. Gómez-Vargas (PAGEPress Publications, 2002)
Rheumatology has come a long way since its origins. Rheumatic conditions are some of the oldest recognized conditions in human and animal remains all around the world. They have been recognized and managed by all medical traditions, even before Hippocrates. Hippocrates wrote on gout and other ill-defined rheumatic conditions, and mentioned for the first time the existence of synovial fluid...